Short virtual nature breaks in the office environment can restore stress: An experimental study. (December 2022) - Ojala, Ann; Neuvonen, Marjo; Kurkilahti, Mika; Leinikka, Marianne; Huotilainen, Minna; Tyrväinen, Liisa
Abstract: Knowledge workers need short breaks during their office hours to relieve stress. We examined the benefits of virtually produced nature environments during afternoon breaks. Knowledge workers (n = 39) visited the Virtual Nature Room a total of nine times. During their 15-min break, the volunteers 1) watched a video (of a forest or water environment) on a TV monitor with related nature sounds, 2) listened to nature sounds (without a video), or 3) as a control condition, sat in the quiet room without audio-visual material. The volunteers responded to the psychological measures, and we measured the heart rate variability during the experiment. All breaks indicated stress reduction in some measures. The video with audio sessions increased the felt restoration more than the audio and the control conditions. The mean heart rate was sensitive to detect slight decrease during video conditions over the control. Some unexpected results such as the decrease of positive emotions and energy level during breaks are discussed. Highlights: Knowledge workers need breaks during working day. All virtual nature breaks enhance stress recovery. The session with the video and audio of nature environment was the most restorative condition. Virtual nature breaks in offices may be useful for workers' relaxation and stress management.